Drug-induced male infertility: a real-world study using FAERS and EudraVigilance databases - Gong, Zhuozhi; He, Jing; Feng, Qiujian; Liu, Dong; Liu, Shengjing (Frontiers in Pharmacology, 2026)
ObjectiveTo systematically identify medications potentially causing male infertility or sperm abnormalities and provide risk alerts for clinical practice.MethodsA pharmacovigilance study was conducted using the FAERS database (Q1 2004–Q2 2025) and EudraVigilance (EV) database (January 2002–October 2025). Adverse events related to male reproductive toxicity were screened using the MedDRA dictionary. Drug safety signals were detected using ROR, PRR, IC, and EBGM, with reliability enhanced through cross-database validation and dechallenge/rechallenge analyses.ResultsThe study included 1,955 FAERS cases and 1,384 from EV, with a median patient age of 35 years and 37% being reproductive-age males (18–44 years). The median time to event onset was 132 days, consistent with the spermatogenic cycle. Cross-validation identified 19 high-risk drugs, including hormonal agents (finasteride, dutasteride, testosterone), antineoplastic drugs (bleomycin, vinblastine, hydroxycarbamide), and antidepressants (citalopram, paroxetine). Finasteride satisfied both dechallenge and rechallenge criteria, providing strong evidence for causality. Signals concentrated in three major categories: genitourinary and sex hormones, dermatological preparations, and antineoplastic agents. Stratified analysis showed that both consumer and healthcare professional reports identified 13 high-risk drugs, with high consistency for major drugs (finasteride, testosterone), confirming result robustness.ConclusionThis pharmacovigilance study identified 19 high-risk drugs for male infertility across hormonal agents, antineoplastic drugs, and antidepressants. These findings underscore pre-prescription, risk-stratified fertility counseling for reproductive-age males, prioritizing sperm cryopreservation before chemotherapy and considering it selectively for 5α-reductase inhibitors, testosterone, or antidepressants.